Dual-band CB-CPW FED on-body antenna for wearable WBAN applications - K, Sajith; J, Gandhimohan; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
In the article introduced the recent split ring resonator (SRR) loaded with bottom grounded coplanar waveguide fed patch element for wire-less body area network or healthcare monitoring applications. The main problems of existing antennas are the low gain and band widths. The metamaterials loaded antenna or split ring resonator loaded antenna had high directive gain and bandwidth. The premeditated patch an-tenna operated at resonated frequency 2.4GHz and 3.5GHz. The implemented outcomes for the magnitude of reflection coefficient are -20dB at 2.4GHz, -18dB at 3.4GHz for non-metamaterials loaded structure,-15dB at 2.3GHz and -22dB at 3.5GHz for metamaterials loaded antenna respectively. The patch requisite characteristic like far-field pattern, magnitude of scattering parameter and voltage standing wave ratio for the proposed antenna is presented.Â Â Â
Keywords: Split Ring Resonator (SRR); Biocompatible Substrate; Conductor Backed Coplanar Waveguide (CBCPW); Wireless Body Area Network (WBAN).